2019
DOI: 10.33073/pjm-2019-016
|View full text |Cite
|
Sign up to set email alerts
|

Hand, Foot, and Mouth Disease Caused by Coxsackievirus A6: A Preliminary Report from Istanbul

Abstract: Hand, foot, and mouth disease (HFMD) is caused by various serotypes of Enterovirus genus. Coxsackievirus A16 (CV-A16) and enterovirus A71 (EV-A71) were known to be the only responsible agents for these epidemics; however, this opinion was challenged after the detection that coxsackievirus A6 (CV-A6) was the responsible species for the outbreak in Finland in 2008. HFMD is frequently seen in Turkey, and no detailed study on its clinical and microbiological epidemiology has previously been reported. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Phylogenetic analysis revealed that the nt sequences from the 3Dpol region belonged to 23 bootstrap-supported clades (recombinant forms (RFs); A–X) in agreement with previous reports ( Figure 2 B) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 43 , 44 , 45 , 46 , 47 ]. Most of the CV-A6/TH strains (84%, 147/174) in this study belonged to the previously described RF-A, while only ~6% (11/174) of the strains were assigned to RF-N (6%), and one strain was classified as RF-H (0.6%).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Phylogenetic analysis revealed that the nt sequences from the 3Dpol region belonged to 23 bootstrap-supported clades (recombinant forms (RFs); A–X) in agreement with previous reports ( Figure 2 B) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 43 , 44 , 45 , 46 , 47 ]. Most of the CV-A6/TH strains (84%, 147/174) in this study belonged to the previously described RF-A, while only ~6% (11/174) of the strains were assigned to RF-N (6%), and one strain was classified as RF-H (0.6%).…”
Section: Resultssupporting
confidence: 91%
“…Since 2008, the coxsackievirus (CV)-A6 strain has become the predominant genotype associated with global outbreaks of atypical hand, foot, and mouth disease (HFMD) [ 1 , 2 , 3 , 4 , 5 , 6 ]. Recent surveillance data have shown the epidemic potential of CV-A6 worldwide, including in Brazil [ 7 ], China [ 8 ], France [ 9 ], Hong Kong [ 10 ], India [ 11 ], Japan [ 12 ], Turkey [ 13 ], Uruguay [ 14 ], and Vietnam [ 15 ]. Severe clinical manifestations, such as vasculitis-like rash and vesiculobullous exanthema, are caused by CV-A6 and have been described in children and adults in several countries, such as Argentina [ 16 ], Brazil [ 17 ], China [ 18 ], Israel [ 19 ], Italy [ 20 ], and Japan [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2008, atypical HFMD outbreaks have been primarily associated with the CV-A6 variant [ 3 , 4 , 5 , 6 , 7 ]. Contemporary surveillance data have demonstrated the potential of the CV-A6 virus for epidemic spread around the world, particularly in Brazil [ 8 ], China [ 9 ], France [ 10 ], Hong Kong [ 11 ], India [ 12 ], Japan [ 13 ], and Turkey [ 14 ]. CV-A6 has been associated with severe clinical symptoms in both children and adults in several nations, including Argentina [ 15 ], Brazil [ 16 ], China [ 17 ], Israel [ 18 ], Italy [ 19 ], and Japan [ 20 ].…”
Section: Introductionmentioning
confidence: 99%